Adult Body Height and Cardiometabolic Disease Risk: The China National Health Survey in Shaanxi - Yuan, Yuan; Zhou, Bo; Wang, Shunan; Ma, Jia; Dong, Fen; Yang, Min; Zhang, Zhixin; Niu, Wenquan (Frontiers in Endocrinology, 2020)
Objectives: Based on data from the China National Health Survey, we aimed to examine the association between body height and cardiometabolic disease (CMD) in a large adult population from Shaanxi province, and further to test whether this association was hinged upon other population characteristics. Methods: This population-based study was conducted in 2014 in Shaanxi Province, China. Utilizing a multi-stage stratified cluster sampling method, total 5905 adults with complete data were eligible for analysis, and 1151 (19.5%) of them had CMD. Of 1151 CMD patients, 895 (15.1%) had 1 disorder and 256 (4.4%) had ≥2 disorders. Results: Using the bi-directional stepwise method and all-subsets regression, 5 factors, age, body mass index, family history of CMD, exercise, and height, constituted the optimal model when predicting CMD risk. Restricted cubic spline regression showed a reduced tendency towards CMD with the increase of body height, with per 10 cm increment in body height corresponding to 14% reduced risk. Ordinal Logistic regression supported the contribution of body height on both continuous and categorical scales to CMD risk before and after adjustment, yet this contribution was significantly confounded by exercise and education, especially by exercise, which can explain 65.4% of total impact. For example, short stature was associated with an increased risk of CMD after multivariable adjustment not including exercise and education (odds ratio, 95% confidence interval, P: 1.42, 1.21 to 1.66, <0.001), and tall stature was associated with a reduced risk (0.77, 0.64 to 0.92, 0.003). Conclusions: Our findings indicate short stature was a risky factor, yet tall stature was a protective factor for CMD in Chinese. Notably, the prediction of short and tall stature for CMD may be mediated by exercise.